Tinjauan Yuridis terhadap Akad Murabahah pada Pembiayaan Hunian Syariah (PHS) di PT.Bank Muamalat Indonesia Tbk. Cabang Kota Banjarmasin - , DESY ARIANI; , Prof. Dr.Abdul Ghofur Anshori, S.H.,M.H., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aim to know application of syariah and settlement of wanprestasi to Murabahah Agreement in Payment of Syariah Dwelling (PHS) in PT. Bank Muamalat Indonesia Tbk., Branch Banjarmasin. This research is normative juridicial research to find the truth by logic of the normative legal scholarship conducted through library research and examines the rule of law (legislation) as well as the legal priniples, in addition based on the library research to completement the data obtained from the field research. This research is presented in a descriptive analytical report, in which the data has been processed and analyzed qualitatively. The Result of this research show that (1) Application of syariah priniples in murabahah agreement in payment of syariah dwelling (PHS) in PT. Bank Muamalat of Indonesia, branch Banjarmasin basically already well implemented in accordance with syariah principles as stipulated in article 2 of syariah banking Act do not contain any such elements riba, maisir, gharar, haram and zalim. In addition, to the application of syariah priciples as well by fatwa national of dewan syariah about murabahah.(2) Wanprestasi settlement of Murabahah agreement in payment of syariah dwelling (PHS) in PT. Bank Muamalat Indonesia, branch Banjarmasin if the customer only do late payments, the bank imposes a penalty but in the case of customers in wanprestasi as in article 15 PHS agreement, the bank has the right to stop the bankâs obligation fulfillment period and then ask the customer to pay or pay off the remaining debt, and selling property warranted by the customer based on the principle of justie. But before the bank with the costumer to the deliberating as the provisions of article 55 of syariah banking act.